Impact of traditional soil burning (guie) on Planosol properties and land‐use intensification in south‐western Ethiopia. (5th March 2015) - Mertens, K.; Tolossa, A. R.; Verdoodt, A.; Dumon, M.; Deckers, J.; Van Ranst, E.; Goss, Michael
Abstract In the Gilgel Gibe catchment in Ethiopia, local farmers intensify land use on Planosols by adjusting a traditional soil burning practice known as guie. The burning practice used to be applied in a cycle of shifting cultivation. However, more recently, farmers burn small plots to make fertile seedbeds for Eucalyptus seedlings in the first year before these trees are transplanted to larger plots. The purpose of this research was to assess the physico‐chemical properties of Planosols that have been subjected to burning over the last 10 yrs and evaluate the contribution of guie to land‐use intensification of these soils. Transect studies and interviews of local farmers, followed by chemical, physical and micromorphological analyses of samples from selected plots were used to compare the soil properties of recently (0–2 yrs) and formerly (3–10 yrs) burnt Planosols with those of unburnt Planosols. The analytical results show that the burning practice improved nutrient availability in the first 2 yrs after guie. Increased amounts of exchangeable aluminium (Al) were reported in the long term. Charge fingerprints illustrate that the nutrient‐buffering capacity of the soil was high shortly after the practice but subsequently decreased with time. Given the population pressure on the formerly extensively used Planosols, it is argued that the current application of guie on small, localized plots for raising Eucalyptus seedlings is well adapted to the local socio‐economic context and promotes land‐use intensification on the Planosols. The increased exchangeable Al content of former Eucalyptus seedbeds merits further in‐depth research into the biophysical sustainability of the burning practice.